2021
DOI: 10.3390/vaccines10010057
|View full text |Cite
|
Sign up to set email alerts
|

After 100 Years of BCG Immunization against Tuberculosis, What Is New and Still Outstanding for This Vaccine?

Abstract: In 2021, most of the world was reasonably still concerned about the COVID-19 pandemic, how cases were up and down in different countries, how the vaccination campaigns were ongoing, and most people were familiar with the speed with which vaccines against SARS-Co-V2 were developed, analyzed, and started to be applied in an attempt to curb the pandemic. Because of this, it may have somehow passed relatively inadvertently for people outside of the field that the vaccine used to control tuberculosis (TB), Mycobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
0
12
1
Order By: Relevance
“…One of recommended strategies to prevent the active TB progression in LTBI group is the vaccination [ 3 ]. However, a single approved BCG vaccine cannot induce enough immune protection against all TB stages [ 4 ]. Hence, to fulfil this gap, multi-stage subunit vaccine composing of active and latent phase antigens has been raised with the concept of stimulating the broad-immune response to both active and latent TB [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of recommended strategies to prevent the active TB progression in LTBI group is the vaccination [ 3 ]. However, a single approved BCG vaccine cannot induce enough immune protection against all TB stages [ 4 ]. Hence, to fulfil this gap, multi-stage subunit vaccine composing of active and latent phase antigens has been raised with the concept of stimulating the broad-immune response to both active and latent TB [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine is one of the potential strategies to combat this infectious stage [ 3 ]. However, a single Bacillus-Calmette-Guérin (BCG) since 1921 provides inadequate immune protection to all TB stages [ 4 ]. To fulfil this gap, a multi-stage subunit vaccine consisting of active and dormancy phase antigens has been proposed based on the idea of inducing the broad immune response against all forms of TB infection [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the product profile of an ideal therapeutic vaccine for TB is unknown. Recombinant BCG strains have received significant attention as potential replacement vaccines for BCG [ 6 , 7 , 8 ]. In contrast to subunit vaccines, live attenuated mycobacterial vaccines elicit a broader immune response and usually do not require an adjuvant.…”
Section: Introductionmentioning
confidence: 99%
“…A topic that warrants discussion is the interaction of the BCG vaccination and the presence of NTM in the environment. The BCG vaccine is known for having lower efficacy for full protection against respiratory TB and, over the past few decades, many attempts have been made to find methods of boosting the BCG vaccine [ 33 ]. Evidence has been shown that the BCG vaccine’s efficacy is directly related to the geographical location of where the vaccine was administered and there is still much to understand regarding why exactly this is the case [ 34 ].…”
Section: Introductionmentioning
confidence: 99%